Strategic Management Practices And Performance Of Malaysian Local Authorities - Ahmad Tajuddin, Ahmad Fadzli (2007)
The study investigates on the strategic management practices in Malaysian local authorities. In this context, the research adopts Wheelen and Hunger's notion of strategic management which constitutes of (a) environmental scanning, (b) strategy formulation, (c) strategy implementation, and (d) evaluation and control. Organizational performance is conceptualized by the efficiency of services that local authorities delivered to the public such as; (a) Certificate of fitness (CF) approval, (b) housing and commercial development plan approval, (c) providing and upgrading infrastructure and public facilities (d) revenue collection, (e) issuing and renewing business licenses (f) keeping the environment healthy and clean, and (g) garbage collection.